1981
DOI: 10.1016/0375-9474(81)90290-6
|View full text |Cite
|
Sign up to set email alerts
|

Reaction dependence of nuclear decay linewidths

Abstract: Various light-and heavy-ion reactions, 20 < E i 100 MeV, have been used to study the reaction dependence of a-decay widths for *Be*(2+, 2.9 MeV) and '60*(1-, 9.6 MeV). Although slight differences (< 20 %) are found for the observed line shapes (F), the resonance widths inferred (F,) are self-consistent and indicate little if any reaction dependence (i 10 %). Near a decay threshold one may expect F < FR by 20 % or more, however, and thus care must be taken in comparing decay widths inferred from nuclear reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…This is the value the reduced width should adopt if the α-particles are fully preformed. For this particular state, it is found that the experimental width is very close to the Wigner limit, again indicating the existence of the cluster structure (Cerny, 1974;Overway et al, 1981). A further signature, not available to the decay of the example states in 8 Be, is the measurement of the dominant decay channel.…”
Section: A Experimental Observablesmentioning
confidence: 82%
“…This is the value the reduced width should adopt if the α-particles are fully preformed. For this particular state, it is found that the experimental width is very close to the Wigner limit, again indicating the existence of the cluster structure (Cerny, 1974;Overway et al, 1981). A further signature, not available to the decay of the example states in 8 Be, is the measurement of the dominant decay channel.…”
Section: A Experimental Observablesmentioning
confidence: 82%
“…(Dated: February 4, 2009) Six proton-emitting states in 19 N e were studied through the inelastic scattering reaction H( 19 N e, p) 19 N e * (p) 18 F . Their energies and widths were derived from the protons detected at zero degree, while proton-proton angular correlations between the detector at zero degree and a segmented annular detector were used to determine their spin value.…”
mentioning
confidence: 99%
“…It would follow that the importance of the interference contribution between the + resonances would be much reduced. In the present paper, we report the results of a new approach developed to study excited states in 19 N e through the reaction 1 H( 19 N e, p) 19 N e * (p) 18 F . Implications to the 18 F (p, α) 15 O rate in novae are subsequently discussed.…”
mentioning
confidence: 99%
See 2 more Smart Citations